The Importance of Disclosure and Transparency in Enhancing Firm Value: A Study on the LQ45 Index - Firman Gani; Inge Lengga Sari Munthe; Nurul Yusyawiru (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2025)
Firm value reflects investors perception of a company's success, which is commonly associated with its stock price. This study aims to examine the effect of Sustainability Report Disclosure, Analyst Coverage and ESG Disclosure on Firm Value, with Firm Age serving as a moderating variable. The research employs a purposive sampling method, involving 12 companies listed in the LQ45 Index of the Indonesia Stock Exchange during the 2021–2023 period. The analytical techniques used include multiple linear regression and moderation analysis through the Moderated Regression Analysis (MRA) method. The results of the multiple regression analysis indicate that Sustainability Report Disclosure and ESG Disclosure do not have a significant impact on Firm Value. Conversely, Analyst Coverage and Firm Age show a significant positive influence on Firm Value. Furthermore, the study finds that Sustainability Report Disclosure, Analyst Coverage, ESG Disclosure and Firm Age collectively have a significant simultaneous effect on Firm Value. Meanwhile, the moderation analysis reveals that Firm Age does not moderate the relationship between either Sustainability Report Disclosure or ESG Disclosure on Firm Value. But, it does moderate the relationship between Analyst Coverage on Firm Value.